2022
DOI: 10.1021/acsomega.2c01278
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Calculation of H2O/CO2/CH4 for Oxygen-Containing Functional Groups in Coal Molecules

Abstract: To investigate the adsorption mechanism of H 2 O, CO 2 , and CH 4 molecules on oxygen-containing functional groups (OFGs) in coal molecules, quantum chemical density functional theory (DFT) simulations were performed to study the partial density of states and Mulliken bond layout of H 2 O molecules bonded to different OFGs. The adsorption energy and Mulliken charge distribution of the H 2 O, CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The C 2 H 2 uptake displayed a good linear relationship with BET surface area and ultramicropore (<0.7 nm) volume (Figure S23). Meanwhile, the oxygen‐containing functional groups can improve the C 2 H 2 adsorption because the enhanced pore surface's polarity could reinforce the interactions between adsorbent and C 2 H 2 molecules with larger quadrupole moments 54,55 . Especially, the C 2 H 2 adsorption capacity positively correlated with the HOCO functionalities (Figure S24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C 2 H 2 uptake displayed a good linear relationship with BET surface area and ultramicropore (<0.7 nm) volume (Figure S23). Meanwhile, the oxygen‐containing functional groups can improve the C 2 H 2 adsorption because the enhanced pore surface's polarity could reinforce the interactions between adsorbent and C 2 H 2 molecules with larger quadrupole moments 54,55 . Especially, the C 2 H 2 adsorption capacity positively correlated with the HOCO functionalities (Figure S24).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the oxygen-containing functional groups can improve the C 2 H 2 adsorption because the enhanced pore surface's polarity could reinforce the interactions between adsorbent and C 2 H 2 molecules with larger quadrupole moments. 54,55 Especially, the C 2 H 2 adsorption capacity positively correlated with the HO C O functionalities (Figure S24). Moreover, the high-resolution N 1s XPS spectrum showed that N-5 species were the major nitrogen functional groups in CSH-2-700 (Table S2 5A).…”
Section: Gas Adsorption and Separation Performance Of Cshsmentioning
confidence: 97%
“…In contrast, only small wave peaks occur on the surfaces of the perfect coal molecules, with a peak of 3.38 electrons/eV. The higher density of states near the Fermi energy level of the defective coal molecule indicates that the electrons on the surface of defective coal molecules are more active. The projection of the electrostatic potential shows that the smallest electrostatic potential value of the single-vacancy-defective coal molecule surface was located at the defects with a value of −0.041 au (Figure (a)); the smallest electrostatic potential value of the double-vacancy-defective coal molecule surface was around the five-ring aromatic cluster with a value of −0.027 au (Figure (b)); the smallest electrostatic potential value of the perfect coal molecule surface was around the whole 2 × 2 aromatic cluster with a value of −0.025 au (Figure (c)). A comparison of the magnitude of the electrostatic potential values on the surfaces of the different coal molecules reveals that the surfaces of the single-vacancy-defective coal molecules have the highest electron density.…”
Section: Resultsmentioning
confidence: 99%
“…The H-bond lengths for Ti@Sn and Fe@Sn are 1.89 and 1.95 Å, respectively, similar to the H-bond lengths reported previously for various oxygen containing functional groups. 75 In addition, the distances between the donor and acceptor atoms in Ti@Sn and Fe@Sn are much shorter than the sum of van der Waals radii of the donor and acceptor atoms and the O-H bond length in H 2 O (ESI †). Furthermore, our Bader charge analysis indicates the shift in electron density: charge on the O atom of water increases while on the C atom of the CO 2 molecule decreases (Table S3, ESI †).…”
Section: Co 2 Reduction In Watermentioning
confidence: 99%